Pengaruh Label Halal, Electronic Word Of Mouth Dan Kualitas Produk Terhadap Keputusan Pembelian Skincare Safi Melalui Brand Image Dan Brand Trust - Didik Gunawan Gunawan (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to determine the effect of halal labels, electronic word of mouth, and product quality on purchasing decisions mediated by brand image and brand trust on consumers who use safi skincare. The effect that we want to know is the direct or indirect effect. This type of research is explanatory research which explains the causal relationship between the variables through hypothesis testing. The sample used in this study amounted to 100 respondents with simple random sampling technique. The test tool used is Partial Least Square (PLS) using SmartPLS 3.0 software. From the results of this test, it can be concluded that the halal label, electronic word of and product quality have a significant effect on brand image. Halal label, electronic word of mouth and product quality have a significant effect on brand trust. Halal label, electronic word of mouth and product quality have no significant effect on purchasing decisions. Brand image and brand trust have a significant effect on purchasing decisions. Halal labels, electronic word of mouth have a significant effect on purchasing decisions with brand image and brand trust as mediating variables. Product quality has no significant effect on purchasing decisions with brand image and brand trust as mediating variables.